STUDI SIMULASI TRANSIEN AKIBAT SAMBARAN PETIR PADA SALURAN DISTRIBUSI 20 KV DI YOGYAKARTA DENGAN BANTUAN EMTP - Hani, Slamet; Sabdullah, Mursid (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2007)
The transient over-voltage phenomenon in an electrical power system caused by weather factors for example rain, lightning and wind, as well as by technical factors for example switching, power electronic and electrical machines. This research was conducted for at distributed transient over-voltage on a 20 kV, and 3 phase 4-wire system, due to thunder pounce. A simple way for the analysis uses EMTP program (Electromagnetic Transients Program) which is a simulation tool to this case (At 20 kV distribution line from Kentungan Power station to Kalasan-Yokyakarta). The results show that transient over-voltage occurred along the distribution lines, and the voltages vary along the distribution line length and the location where the thunder struck.